Development of Interactive Learning Media in Science Subjects of Class VIII SMP/MTS - Dzaki, Ahmad; Zuwirna, Zuwirna; Darmansyah, Darmansyah; Amilia, Winanda (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research is motivated by the low student learning outcomes, due to the lack of interactive multimedia use in the teaching and learning process besides the lack of student interest in learning, because it uses the same learning model. The research aims to develop valid and practical Interactive Learning Media in Class VIII SMP/MTs Science Subjects. This research is a development research (R&D) with a 4D development model. The results of learning media development research by media validator 1 obtained